Nitzotz: the Spark of resistance in Kovno ghetto and Dachau-Kaufering Concentration Camp - Weinrib, Laura M.; Weinrib, Estee (Religion, theology, and the Holocaust, 2009)
Pt. 1. The voices of resistance -- pt. 2. Nitzotz